Prospects for Higgs and di-Higgs measurements at the ATLAS experiment - Alessandra Betti (SciPost Physics Proceedings, 2022)
The large dataset of about 3000 $\rm{fb}^{-1}$ that will be collected at the High Luminosity LHC (HL-LHC) will be used to measure Higgs boson processes in detail. This large dataset will also provide sensitivity to di-Higgs processes and will allow for the improvement of the constraints on the Higgs boson self coupling. Studies based on current ATLAS analyses using LHC Run 2 data have been carried out to understand the expected precision and limitations of the Higgs and di-Higgs measurements at the HL-LHC. This paper presents the ATLAS prospects for Higgs and di-Higgs results at the HL-LHC.